Community-Based Intelligent Blood Glucose Management for Older Adults With Type 2 Diabetes Based on the Health Belief Model: Randomized Controlled Trial - Anqi Zhang; Jinsong Wang; Xiaojuan Wan; Ziyi Zhang; Shuhan Zhao; Shuo Bai; Yamin Miao; Shuang Yang; Xue Jiang (JMIR mHealth and uHealth)
Abstract BackgroundThe number of older patients with type 2 diabetes (T2D) is increasing, and effective self-management is crucial for controlling disease progression and its complications. ObjectiveWe designed a home telemedicine intervention that combines telemedicine with health education based on the Health Belief Model (HBM). This study evaluated its effectiveness on self-management in older patients with T2D. MethodsBetween March and April 2022, we recruited 198 community-dwelling patients with T2D aged 65 years and older. Patients were randomly assigned to either a control group, which received a conventional diabetes management program, or an intervention group, which received a home telemedicine intervention with a health education program based on the HBM. The intervention lasted 6 months. The primary outcome measured was glycosylated hemoglobin (HbA1c ResultsA total of 96.5% (191/198) of patients completed the study. From baseline to 6 months, HbA1c ConclusionsHome telemedicine interventions incorporating health education based on the HBM can provide significant benefits for community-dwelling older patients with T2D, potentially offering new avenues for chronic disease prevention and management. However, future large-scale studies are required to further assess their effectiveness and feasibility.